Malian field isolates provide insight into Plasmodium malariae intra-erythrocytic development and invasion. - Francois Dao; Amadou Niangaly; Fanta Sogore; Mamadou Wague; Djeneba Dabitao; Siaka Goita; Aboubacrin S Hadara; Ousmaila Diakite; Mohamed Maiga; Fatoumata O Maiga; Chantal Cazevieille; Cecile Cassan; et al. (PLoS Neglected Tropical Diseases)
Plasmodium malariae is the third most prevalent human malaria parasite species and contributes significantly to morbidity. Nevertheless, our comprehension of this parasite's biology remains limited, primarily due to its frequent co-infections with other species and the lack of a continuous in vitro culture system. To effectively combat and eliminate this overlooked parasite, it is imperative to acquire a better understanding of this species. In this study, we embarked on an investigation of P. malariae, including exploring its clinical disease characteristics, molecular aspects of red blood cell (RBC) invasion, and host-cell preferences. We conducted our research using parasites collected from infected individuals in Mali. Our findings revealed anaemia in most of P. malariae infected participants presented, in both symptomatic and asymptomatic cases. Regarding RBC invasion, quantified by an adapted flow cytometry based method, our study indicated that none of the seven antibodies tested, against receptors known for their role in P. falciparum invasion, had any impact on the ability of P. malariae to penetrate the host cells. However, when RBCs were pre-treated with various enzymes (neuraminidase, trypsin, and chymotrypsin), we observed a significant reduction in P. malariae invasion, albeit not a complete blockade. Furthermore, in a subset of P. malariae samples, we observed the parasite's capability to invade reticulocytes. These results suggest that P. malariae employs alternative pathways to enter RBCs of different maturities, which may differ from those used by P. falciparum.